Compact Multiband Circularly Polarized Filtering Antenna - Kiran Sonawane; Pravin Patil (Journal of Studies in Science and Engineering)
A miniature circularly polarised filtering antenna device is presented here. The device has an impeccably circular radiating patch coupled with pins to stripline circuits with open-loop ring resonators. In the proposed design, the filter's last stage acts as a radiating patch and has a low profile of 0.57λ0 x 0.57λ0 x 0.07λ0 at a centre frequency of 4.26 GHz. The codesigned filtering circuit improves the wide impedance bandwidth and axial ratio of 3 dB bandwidth. The filtenna was designed, fabricated and measured, gaining more than 2.5 dB and S11< -14 dB for an impedance bandwidth of 700 MHz from 4.1 to 4.8 GHz. Impedance bandwidth, which is needed for wireless applications, is 13.33%. The developed circularly polarised codesign filtering antenna was verified using full wave models and testing. The filtering antenna is useful for biomedical applications such as wearable and 5G applications